Accordance and conflict between religious and scientific precautions against COVID-19 in 27 societies - Samore, Theodore (Religion, brain & behavior, 2025)
Meaning-making systems underlie perceptions of the efficacy of threat-mitigating behaviors. Religion and science both offer threat mitigation, yet these meaning-making systems are often considered incompatible. Do such epistemological conflicts swamp the desire to employ diverse precautions against threats? Or do individuals—particularly individuals who are highly reactive to threats—hedge their bets by using multiple threat-mitigating practices despite their potential epistemological incompatibility? Complicating this question, perceptions of conflict between religion and science likely vary across cultures; likewise, pragmatic features of precautions prescribed by some religions make them incompatible with some scientifically-based precautions. The COVID-19 pandemic elicited diverse precautions thus providing an opportunity to investigate these questions. Across 27 societies from five continents (N = 7,844), in the majority of countries, individuals’ practice of religious precautions such as prayer correlates positively with their use of scientifically-based precautions. Prior work indicates that greater adherence to tradition likely reflects greater reactivity to threats. Unsurprisingly given associations between many traditions and religion, valuing tradition is predictive of employing religious precautions. However, consonant with its association with threat reactivity, we also find that traditionalism predicts adherence to public health precautions—a pattern that underscores threat-avoidant individuals’ apparent tolerance for epistemological conflict in pursuit of safety.